1997
DOI: 10.1161/01.atv.17.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Ser447stopMutation in Lipoprotein Lipase Is Associated With Elevated HDL Cholesterol Levels in Normolipidemic Males

Abstract: This report describes the association between a frequent mutation in the lipoprotein lipase (LPL) gene and HDL cholesterol levels. It concerns a previously described defect that predicts a premature truncation of the LPL protein (447stop). We determined the frequency of this mutation in three groups of healthy men with low-, middle-, and upper-decile HDL cholesterol. The number of carriers of the 447stop allele was significantly greater in the high HDL group than in either the groups with normal HDL (P = .017)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 34 publications
6
52
1
Order By: Relevance
“…The LPL S447X polymorphism has been associated with higher LPL activity, lower TG, and higher HDL-C levels in several studies (Wittrup et al 1999;Kuivenhoven 1997), which is compatible with the higher LPL activity of S447X in a transfection study (Kozaki et al 1993;Zhang et al 1996). However, that association was not found in this study, probably because of the relatively small sample size.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The LPL S447X polymorphism has been associated with higher LPL activity, lower TG, and higher HDL-C levels in several studies (Wittrup et al 1999;Kuivenhoven 1997), which is compatible with the higher LPL activity of S447X in a transfection study (Kozaki et al 1993;Zhang et al 1996). However, that association was not found in this study, probably because of the relatively small sample size.…”
Section: Discussionsupporting
confidence: 79%
“…D442G and IVS14 ϩ 1G Ͼ A of the CETP gene were determined as described elsewhere (Inazu et al 1994). The S447X polymorphism of the LPL gene was determined using MnlI (Daiichi Chemicals) digestion, as described by Kuivenhoven et al (1997). The HL promoter Ϫ250G/A polymorphism was determined using DraI (Toyobo, Tokyo, Japan) digestion, as described by Zambon et al (1998).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the wild type, the LPL activity associated with the X447 mutation was higher in one, lower in another, but comparable in three studies [reviewed in 22]. In association studies, although the X447 allele has been reported to be associated with a favorable lipid profile in some studies [7][8]22] the results have not been confirmed in other studies [15]. Similarly, the association of the S447X polymorphism with CAD is inconsistent [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Several common LPL genetic variants have been widely studied, and among them HindIII in intron 8 (T→G at position 481), and S447X in exon 9 are of particular interest because of their common occurrence (25% and 9% of the less common alleles, respectively in most populations) and their associations with plasma lipid profile [6][7][8][9][10][11] and susceptibility to CAD [10][11][12][13][14][15] in several studies, although some inconsistent results have also been reported [16][17][18]. Since the HindIII polymorphism is located in the middle of intron 8, it is not considered to be functional but rather in linkage disequilibrium with a putative functional variant.…”
Section: Introductionmentioning
confidence: 99%
“…Kuivenhoven et al [32] found significantly greater number of carriers of the S447X in the high HDL-C group than in either the groups with normal or low HDL-C.…”
Section: Discussionmentioning
confidence: 95%